Predictability in orbital reconstruction. A human cadaver study, part III: Implant-oriented navigation for optimized reconstruction. Issue 10 (December 2015) - Dubois, Leander; Essig, Harald; Schreurs, Ruud; Jansen, Jesper; Maal, Thomas J.J.; Gooris, Peter J.J.; Becking, Alfred G.
Abstract: Navigation-assisted orbital reconstruction remains a challenge, because the surgeon focuses on a two-dimensional multiplanar view in relation to the preoperative planning. This study explored the addition of navigation markers in the implant design for three-dimensional (3D) orientation of the actual implant position relative to the preoperative planning for more fail-safe and consistent results. Pre-injury computed tomography (CT) was performed for 10 orbits in human cadavers, and complex orbital fractures (Class III/IV) were created. The orbits were reconstructed using preformed orbital mesh through a transconjunctival approach under image-guided navigation and navigation by referencing orientating markers in the implant design. Ideal implant positions were planned using preoperative CT scans. Implant placement accuracy was evaluated by comparing the planned and realized implant positions. Significantly better translation (3.53 mm vs. 1.44 mm, p = 0.001) and rotation (pitch: −1.7° vs. −2.2°, P  = 0.52; yaw: 10.9° vs. 5.9°, P  = 0.02; roll: −2.2° vs. −0.5°, P  = 0.16) of the placed implant relative to the planned position were obtained by implant-oriented navigation. Navigation-assisted surgery can be improved by using navigational markers on the orbital implant for orientation, resulting in fail-safe reconstruction of complex orbital defects and consistent implant positioning.